2003
DOI: 10.1258/000456303770367252
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of renal function in kidney donors using serum cystatin C and β2-microglobulin

Abstract: Using critical values, serial measurement of serum creatinine was better than serum B2M in detecting reduced renal function. Because of its large intraindividual variation, serial serum cystatin C estimation was very poor in detecting reduced renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The authors suggest that cystatin C is more sensitive than creatinine as a marker of GFR reduction. A different conclusion was drawn by John et al [38], who, after 10 days in 28 kidney donors after nephrectomy, found GFR reduction, a 40% rise in creatinine concentration, and a 31% increase in cystatin C level. The authors think that cystatin C level shows high individual changeability and, therefore, it is not reliable to be used for the assessment of renal function impairment in these patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The authors suggest that cystatin C is more sensitive than creatinine as a marker of GFR reduction. A different conclusion was drawn by John et al [38], who, after 10 days in 28 kidney donors after nephrectomy, found GFR reduction, a 40% rise in creatinine concentration, and a 31% increase in cystatin C level. The authors think that cystatin C level shows high individual changeability and, therefore, it is not reliable to be used for the assessment of renal function impairment in these patients.…”
Section: Discussionmentioning
confidence: 78%
“…In the available literature we found no reports on the use of serum cystatin C level for the assessment of glomerular filtration in congenital solitary kidney patients. Rare reports have only described unilateral kidney patients after nephrectomy [37,38]. Kasiske et al [8], who conducted a meta-analysis of publications concerning the function of the only kidney after nephrectomy, concluded that the function is not impaired.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several previously published researches including Laterza et al [24], Le Bricon et al [25], Bianchi et al [26] and John et al [27] had concluded that serum cystatin C and beta2 microglobulin were easily applicable, highly sensitive indicators for AKI in their study when compared to routinely used serum creatinine.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies demonstrated the superiority of S. cystatin C compared with S.creatinine in the evaluation of GFR, especially when there is a minor reduction in GFR. [16171819] They found that S. cystatin C could detect renal dysfunction 1-2 days before S.creatinine. [20] However, other studies showed that S. cystatin C did not rise earlier than S. creatinine and was a poor biomarker for AKI.…”
Section: Introductionmentioning
confidence: 99%